2004
DOI: 10.1152/ajplung.00116.2003
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H oxidase mediates the endothelial barrier dysfunction induced by TNF-α

Abstract: We tested the hypothesis that the NAD(P)H oxidase-dependent generation of superoxide anion (O2-*) mediates tumor necrosis factor-alpha (TNF)-induced alterations in the permeability of pulmonary microvessel endothelial monolayers (PMEM). The permeability of PMEM was assessed by the clearance rate of Evans blue-labeled albumin. The NAD(P)H oxidase subcomponents p47phox and p22phox were assessed by immunofluorescent microscopy and Western blot. The reactive oxygen species O2-* was measured by the fluorescence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 37 publications
7
75
0
2
Order By: Relevance
“…TNF-α induces NADPH oxidase-dependent superoxide production through several mechanisms, including increase in p22phox expression, and translocation of p47phox [37]. Our results have further revealed that TNF-α may activate the NADPH oxidase system by modulating the expression of Nox subunits.…”
Section: Discussionsupporting
confidence: 61%
“…TNF-α induces NADPH oxidase-dependent superoxide production through several mechanisms, including increase in p22phox expression, and translocation of p47phox [37]. Our results have further revealed that TNF-α may activate the NADPH oxidase system by modulating the expression of Nox subunits.…”
Section: Discussionsupporting
confidence: 61%
“…Plasma levels of platelet activating factor (PAF) are elevated in hypercholesterolemia [29], PAF is known to stimulate granulocytes to release cytokines such as TNF-α [30] which stimulates nicotinamide adenine dinucleotide phosphate oxidase (NADPH-oxidase) in the endothelial cells to generate ROS [31] and INF-γ [32] which activate granulocytes to generate ROS [33]. In addition hypercholesterolemia increases synthesis of arachidonic acid and prostaglandins [34].…”
Section: Discussionmentioning
confidence: 99%
“…68 Nevertheless, Rac1 activation also causes loss of cellcell contacts upon stimulation of endothelial cells with VEGF, PAF and TNF-a, as well as clustering of vascular cell adhesion molecule (VCAM)-1. 25,[69][70][71][72][73] These data seem to be conflicting; however, they in fact underlie the importance of understanding the particular GEFGTPase-effector complexes that are locally activated under resting and inflammatory conditions. We have summarized this in Figure 2.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasesmentioning
confidence: 99%